Quantifying bilateral asymmetry in competitive front crawl swimming - Barden, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Studies show that the different phases of the arm stroke cycle in front crawl swimming are bilaterally asymmetric [1,3], and that asymmetry is affected by speed, arm dominance and bilateral differences in body roll [4]. However, little is known about the effect of asymmetry on performance, and given its importance to propulsion mechanics, a simple method to quantify arm asymmetry in competitive front crawl swimming is needed. Therefore, the purpose of this study was to quantify bilateral asymmetry in a group of elite front crawl swimmers at two different speeds using two different stroke-related spatiotemporal parameters. Methods: Eight swimmers (6 female, 2 male; 17.9 ± 0.86 yrs) performed front crawl for 2 x 200 m repetitions in a 25 m pool at two different speeds: 1) 91% and 2) 110% of critical speed. Stroke frequency (SF) and stroke length (SL) were recorded independently for both arms for each length of each 200 m repetition. An asymmetry index (ASI), previously used to assess gait asymmetry [2], quantified individual asymmetries for SF and SL according to the following equation: ASI (%) = [Xr-Xl)/0.5(Xr+Xl)] x100 where Xr and Xl are the values of the specific stroke variable (SF or SL) measured for the right and left arm, respectively. Group asymmetries were calculated using the absolute value of Xr - Xl. For the purpose of this study, a stroke (right or left) was defined as consisting of one half of a complete stroke cycle (synonymous with a step in walking). A paired Student`s t-test compared mean absolute ASI values for SF and SL between the two 200`s. Results: A range of asymmetries were found (SF: -7.3 to 9.8%; SL: -10.0 to 10.8%), with some participants being more asymmetric than others. The group was divided equally in terms of right (4) vs. left (4) asymmetry. No significant differences in absolute ASI were found for either SF or SL between the two speeds. Discussion: The findings show that arm asymmetries in front crawl swimming can be easily quantified by adopting existing gait asymmetry indices to the cyclic motion of swimming. Of particular interest was the finding that no ASI differences existed between the two speeds, and that positive SL asymmetries (right arm > left arm) were associated with negative SF asymmetries (right arm < left arm), and vice versa. This indicates that longer stroke times on one side are associated with longer stroke lengths on the same side (and vice versa), demonstrating the important bilateral relationship between stroke phase duration and distance per stroke. It is hoped that future studies will employ the method used here to investigate the effects of breathing, body roll and lateral dominance on bilateral asymmetry in competitive front crawl swimming.